Binding to Amyloid‐β Protein by Photothermal Blood‐Brain Barrier‐Penetrating Nanoparticles for Inhibition and Disaggregation of Fibrillation. (16th July 2021) - Geng, Hao; Pan, Yu‐chen; Zhang, Ran; Gao, Dong; Wang, Zijuan; Li, Boying; Li, Ning; Guo, Dong‐sheng; Xing, Chengfen
Abstract: Excess accumulation of amyloid‐β (Aβ) protein in the brain is the primary pathogenesis of Alzheimer's disease (AD). Inhibition of Aβ fibrillation and disaggregation of Aβ fibrils is an attractive therapeutic and preventive strategy for Aβ‐induced AD. Here, near infrared (NIR) light‐responsive nanoparticles (NPs) composed of amphiphilic guanidinocalix[5]arene (GC5A), 4‐(dodecyloxy)benzamido‐terminated methoxy poly(ethylene glycol), and photothermal conjugated polymer PDPP are fabricated. The NIR light‐responsive NPs can efficiently penetrate the blood‐brain barrier (BBB), inhibit amyloid‐β 42 (Aβ42) fibrillation, and disaggregate fibrils after NIR light irradiation. Through the advantage of containing GC5A, the NPs exhibit extremely strong binding affinity for the Aβ42 protein. Interestingly, upon NIR light irradiation, benefiting from the high photothermal conversion efficiency of PDPP, NPs generate local heat and effectively promote the BBB permeability. Moreover, NPs are multifunctional platforms for the inhibition of Aβ42 fibrillation and disaggregation of fibrils after irradiation with NIR light, distinctly reducing cytotoxicity and eliminating Aβ42 plaques in the hippocampus of AD mice. Hence, NPs provide an interesting strategy for the inhibition and disaggregation of Aβ42 fibrillation and present an excellent therapeutic strategy for amyloidosis. Abstract : The near infrared (NIR) light‐responsive nanoparticles (NPs) composed of calixarene (GC5A), and a conjugated polymer (PDPP) exhibit efficient permeability through the blood‐brain barrier and inhibit and disaggregate Aβ42 fibrillation. Upon NIR light irradiation, the NPs generate local heat and efficiently disaggregate Aβ42 fibrils, leading to the cytotoxicity of Aβ42 fibrils reduce, and eliminate Aβ42 plaques in Alzheimer's disease mouse brain.